Metabolic syndrome and calcium: the effects on body composition and biochemical parameters among premenopausal women - Arıtıcı, Gözde; Bas, Murat (Progress in Nutrition, 2018)
Aims: The objective of this study is to investigate the association of the dietary calcium intake with the risk of metabolic syndrome among the premenopausal women. Methods: The cross-sectional study was conducted between August and December 2015.  One hundred and forty-six premenopausal women, from 19 to 52 years old, participated in the study. The diet section of this study was based on the 3-day self-reported nutrient intake of the recipients. All participants agreed to participate and be submitted to clinical, dietary, anthropometric and biochemical evaluations at the Endocrinology Department at Baskent University Hospital in Ankara. Multiple logistic regression models were used to estimate multivariable odds ratios (ORs) and 95% CIs comparing different dietary intake levels of calcium. Results: Participants in ‘the group without metabolic syndrome’ exhibited significantly higher BMI, waist circumferences, body fat and visceral fat (p